PENERAPAN MODEL PBL PENDEKATAN TPACK MEDIA INTERAKTIF UNTUK MENINGKATKAN AKTIVITAS DAN BERPIKIR KRITIS SISWA SD - Edy Wasono; Miluwati, Miluwati; Daimul Hasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to improve teacher activity, student activity, critical thinking skills and student learning outcomes using the PBL model with the TPACK approach based on interactive media. This research used PTK which was carried out in 3 meetings. The research was carried out in class IV of SDN 1 Kaloran Temanggung in the 2023/2024 academic year. The research results showed that the teacher's activity at the first meeting got a score of 21, the second meeting got a score of 24, and the third meeting got a score of 27. From the first to the third meeting, student activity increased. The classical completeness of students' learning outcomes at the first meeting increased by 30% to 100%. Their critical thinking skills increased by 26% to 100% at the third meeting. Based on these results, it can be concluded that the combination of the PBL learning model with the TPACK approach based on interactive media can increase teacher activity, student activity, learning outcomes and critical thinking skills for class IV students at SDN 1 Kaloran.